" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
b) (3 - 7) * (15 - 6) =(-4)*9= -36
c) (17-5) : (-3) =12:(-3)= -4
e) (-5) * 2 * (-7) = -10*(-7)=70
f) (-3) * (-2) * (-4) =6*(-4)= -24
g) ((-6) * (-5)) : (-15) =30:(-15)= -2
i) (-5) * (-2) + 6 * (-3) =10-18= -8
j) -25: (-2 + 7) - 3 = -25:5-3= -5-3= -8
k) ((-8 + 2) : 3 ) * (8 - 15) =(-6:3)*(-7)= -2*(-7)=14
m) (-4 - 5 + 2)² =(-9+2)²=(-7)²=49
n) (3 - 7 + 2)² =(-4+2)²=(-2)²=4
o) (-5 +2) ² - (-2) * (-5) ² =(-3)²-(-2)*25=9-(-50)=9+50=59
b) (3-7)*(15-6)=(-4)*9= -36
c) (17-5):(-3)=12:(-3)= -4
d) -23-4 -27
---------= ----- = 3
-28+19 -9
e) (-5)*2*(-7)= -10*(-7)=70
f) (-3)*(-2)*(-4)= 6*(-4)= -24
g) ((-6)*(-5)):(-15)= 30:(-15)= -2
i) (-5)*(-2)+6*(-3)= 10+(-18)= -8
j) -25:(-2+7)-3= -25:5-3= -5-3= -8
k) ((-8+2):3)*(8-15)= (-6:3)*(-7)= -2*(-7) = 14
l) 25-(-3) 28 28
----------- = --------= ----- =2
-2*(-15+8) -2*(-7) 14
m) (-4-5+2)^2= (-7)^2= 47
n) (3-7+2)^2= (-2)^2= 4
o) (-5+2)^2 -(-2)*(-5)^2= (-3)^2+2*25= 9+50= 59
p) (-5)^2-(-1)^2 25+ 1^2 25+1 26
-------------- = ------- = ----- = ----- = -6
(-2)*3+2 -6+2 -4 -4
Pozdrawiam ;)